1999
DOI: 10.1021/la9817314
|View full text |Cite
|
Sign up to set email alerts
|

Monolayers of Thiol-Terminated Dendrimers on the Surface of Planar and Colloidal Gold

Abstract: The synthesis of fourth-generation poly(amido−amine) (PAMAM) dendrimers having terminal groups partially or fully functionalized with thiol groups is described. These thiolated dendrimers form stable monolayers on planar Au substrates. X-ray photoelectron spectroscopy studies reveal that most of the thiol groups on dendrimers having 20% of their terminal primary amine groups functionalized can directly interact with the Au surface. This suggests that the dendrimer molecules are flexible and arrange themselves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 39 publications
6
90
0
Order By: Relevance
“…PEI2-GNP conjugates were synthesized by reducing hydrogen tetrachloroaurate with sodium borohydride (39)(40)(41)(42) in the presence of the thiol-modified PEI2 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…PEI2-GNP conjugates were synthesized by reducing hydrogen tetrachloroaurate with sodium borohydride (39)(40)(41)(42) in the presence of the thiol-modified PEI2 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…This can be done by adding different surfactants on the surface of the particles, thus making the surface non-polar and more compatible with the organic solvents used in inks. Typical surfactants include organic acids [8] and acid anhydrides, thiols, [9] organic phosphates [10], and polymers with reactive polar functional groups [11,12]. In order to achieve sufficient mechanical durability, both synthetic products and natural fatty acids are used as binders of the solid components in the printed patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic wedges can be coupled to the support through the focal point (Figure 11(a)), through aromatic fragments in the interior of the dendron (Figure 11(b)), or through the peripheral functionalities (Figure 11(c)), whereas dendrimers are usually immobilized through the peripheral functional groups. In addition, a covalent binding through the focal point onto a previously activated substrate usually leads to a dendron monolayer ( Figure 11 A common method to dendronize gold surfaces is by chemisorption of a thiol moiety [95] using focally-substituted organothiol dendrons. Gorman et al [96] found that as the number of hyperbranches in the thiolate dendron increased from one to three, the dendron adlayers became initially less and then more permeable.…”
Section: Organization Of the Dendron Layermentioning
confidence: 99%